2000
DOI: 10.1034/j.1600-048x.2000.310212.x
|View full text |Cite
|
Sign up to set email alerts
|

Prey selection and foraging performance of breeding Great Tits Parus major in relation to food availability

Abstract: We studied the nestling diet and the foraging performance of Great Tits in relation to prey abundance in the field. Numerous experimental studies present data on foraging decisions in captive Great Tits. Little is, however, known about prey selection in the field in relation to the food available and the consequences this has for the food delivery rate to nestlings. Since the foraging performance of the parents is one of the main determinants of fledging weight and juvenile survival, foraging behaviour is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 39 publications
9
188
0
2
Order By: Relevance
“…This suggests that the parents of parasitised broods put a special effort into getting more caterpillars. Caterpillars are preferred prey of Blue Tits (Blondel et al 1991, Perrins 1991, Bańbura et al 1999) but the breeding tits need much effort to collect them in many poor habitats including the present study area (Blondel et al 1991, Bańbura et al 1994, Grieco 1999, 2002, Naef-Daenzer & Nager 2000. A lack of a consistent pattern in feeding on spiders and other prey suggests that they are collected more opportunistically than caterpillars.…”
Section: Discussionmentioning
confidence: 77%
“…This suggests that the parents of parasitised broods put a special effort into getting more caterpillars. Caterpillars are preferred prey of Blue Tits (Blondel et al 1991, Perrins 1991, Bańbura et al 1999) but the breeding tits need much effort to collect them in many poor habitats including the present study area (Blondel et al 1991, Bańbura et al 1994, Grieco 1999, 2002, Naef-Daenzer & Nager 2000. A lack of a consistent pattern in feeding on spiders and other prey suggests that they are collected more opportunistically than caterpillars.…”
Section: Discussionmentioning
confidence: 77%
“…1988, Tinbergen & Verhulst 2000. Great Tits typically behave as singleprey loaders (Gibb & Betts 1963, Naef-Daenzer et al . 2000, and most visits to the nest are for feeding young (Kluijver 1950, Eguchi 1980.…”
mentioning
confidence: 99%
“…The abundance, due to huge numbers of caterpillars of Tortrix viridana (Lepidoptera, Tortricidae) in the oakwood, was much higher in 1993, 1997, and 1999 than in the other years, when this moth was less frequent. In the reafforestation area, samples of 19931994199719981999200020012002Mean 1993-200219931994199719981999200020012002Mean 1993-200219931994199719981999200020012002Mean 1993-200219931994199719981999200020012002Mean 1993-2002 arthropods were very scarce in the breeding seasons considered. In the oakwood the resource peak occurred between the end of April and the first two weeks of May, overlapping well with nestling growth, while in the reafforestation we were not able to find any type of peak, since the samples were invariably scarce.…”
Section: Arthropod Abundancementioning
confidence: 99%
“…The nestling period in Sicilian oakwood generally matches well the availability of food, and this applies to caterpillars as well as to other prey items; matching the period of maximum availability of caterpillars is crucial for maximizing the energy flow to the nest, which has in turn important consequences for the breeding success of tits (van Noordwijk et al, 1995). According to Zandt et al (1990), Blondel et al (1990) and Banbura et al (1994), the proportion of caterpillars in the food of nestlings in Corsican populations is usually lower than in the mainland, but Naef-Daenzer et al (2000) reported that spiders may outnumber caterpillars in the diet of the great tit in the early breeding season. Both in continental and Corsican populations, the timing of breeding is synchronized with the peak in caterpillar abundance, so that Banbura et al (1994) considered caterpillars to be the major factor influencing life-history traits of Corsican blue tits.…”
Section: Breeding Traitsmentioning
confidence: 99%
See 1 more Smart Citation